Operational performance of Ecuadorian industrial companies - Yaguache Aguilar, María Fernanda; Higuerey Gómez, Angel Alexander; Robles Valdes, Isabel María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Companies operating in highly competitive environments have generated important changes in the way they manage and control their costs. The financial information of the dairy production companies in Ecuador was used and three performance measures were applied: Throughput, net profit and return on investment for an industrial company. It was observed that the Throughput tends to increase moderately without affecting the net income, despite the fact that there have been progressive increases or decreases in operating expenses and inventories. This leads to the growing generation of money in the coming financial years.